Effect of laser-focusing conditions on propagation and monoenergetic electron production in laser-wakefield accelerators - Thomas, A; Najmudin, Z; Mangles, S; Murphy, C; Dangor, A; Kamperidis, C; Lancaster, K; Mori, W; Norreys, P; Rozmus, W; Krushelnick, K (2007)
The effect of laser-focusing conditions on the evolution of relativistic plasma waves in laser-wakefield accelerators is studied both experimentally and with particle-in-cell simulations. For short focal-length (w0<λp) interactions, beam breakup prevents stable propagation of the pulse. High field gradients lead to nonlocalized phase injection of electrons, and thus broad energy spread beams. However, for long focal-length geometries (w0>λp), a single optical filament can capture the majority of the laser energy and self-guide over distances comparable to the dephasing length, even for these short pulses (cτ λp). This allows the wakefield to evolve to the correct shape for the production of the monoenergetic electron bunches, as measured in the experiment. © 2007 The American Physical Society.